دور مستشار التوجيه المدرسي في التخفيف من قلق امتحان الرياضيات لدى تلاميذ البكالوريا -دراسة ميدانية بثانوية قطوش خليفة بلدية برهوم ولاية المسيلة- - هبوب اسمهان; يوسفي حنان; اشراف: كتفي عزوز (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة إلى الكشف عن دور مستشار التوجيه في التخفيف من قلق امتحان الرياضيات(بأبعاده الأربعة) لدى تلاميذ البكلوريا (تدخل ارشادي مقترح)-دراسة ميدانية بثانوية قطوش خليفة بلدية برهوم ولاية المسيلة-، حيث اعتمدنا المنهج الوصفي التحليلي بالطريقة الاستكشافية في مجريات الدراسة، واخترنا عينة عشوائية قدرت ب (70) تلميذا وتلميذة، وتم الاستعانة بمقياس عدنان وإبراهيم (1994) لجمع البيانات، واعداد برنامج ارشادي للتخفيف من قلق امتحان الرياضيات، وللتحقق من صحة الفرضيات استخدمنا الأساليب الإحصائية التالية: المتوسطات الحسابية، الانحرافات المعيارية، التكرارات،T-test لحساب الفروق. وتوصلت الدراسة إلى النتائج التالية: - مستوى قلق امتحان الرياضيات مرتفعا لدى تلاميذ السنة الثالثة ثانوي. - مستوى القلق المرتبط بمحتوى تعلم الرياضيات مرتفعا لدى تلاميذ السنة الثالثة ثانوي. - مستوى القلق المرتبط بحصة الرياضيات وأداء الواجبات مرتفعا لدى تلاميذ السنة الثانية ثانوي. - مستوى القلق المرتبط بالامتحان وتبعاته مرتفعا لدى تلاميذ السنة الثالثة ثانوي. - مستوى القلق المرتبط بالاستجابات الفسيولوجية والانفعالية المصاحبة لقلق امتحان الرياضيات متوسطا لدى تلاميذ السنة الثالثة ثانوي. الكلمات المفتاحية: مستشار التوجيه، قلق امتحان الرياضيات، برنامج ارشادي مقترح، تلاميذ البكالوريا. Abstract: The study aimed to investigate the role of the guidance counselor in reducing mathematics exam anxiety among baccalaureate students (a proposed counseling intervention) – a field study conducted at Katoush Khalifa Secondary School, Barhoum Municipality, M’sila Province. The descriptive-analytical method was employed using an exploratory approach. A random sample of 70 male and female students was selected. The Adnan & Ibrahim (1994) scale was used for data collection, and a counseling program was developed to alleviate mathematics exam anxiety. To verify the hypotheses, the following statistical methods were used: arithmetic means, standard deviations, frequencies, and the T-test for measuring differences. The study yielded the following results: • The level of mathematics exam anxiety is high among third-year secondary school students. • The level of anxiety related to the content of mathematics learning is high among third-year secondary school students. • The level of anxiety related to mathematics class and completing assignments is high among second-year secondary school students. • The level of anxiety related to the exam and its consequences is high among third-year secondary school students. • The level of anxiety related to physiological and emotional responses associated with mathematics exam anxiety is moderate among third-year secondary school students. Keywords: Guidance Counselor, Mathematics Exam Anxiety, Proposed Counseling Program, Baccalaureate Students.